2015
DOI: 10.1007/s10815-015-0552-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural markers of quality are impaired in human metaphase II aged oocytes: a comparison between reproductive and in vitro aging

Abstract: These data demonstrated that aging is related to decay of oocyte ultrastructural quality, and that oocytes from elder women are more sensitive to prolonged culture (IvA) than the oocytes from younger women. These morphological results should be considered when applying ART in aged patients, rescue ICSI, or artificial oocyte activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 84 publications
5
59
1
Order By: Relevance
“…As previously stated, if fertilization does not occur within the appropriate period, unfertilized oocytes remain in the oviduct or culture medium and undergo oocyte aging, which impairs oocyte competence . In our facility, the percentage of blastocysts gradually worsened in a time‐dependent manner over a 5‐hour period before ICSI (data not shown).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As previously stated, if fertilization does not occur within the appropriate period, unfertilized oocytes remain in the oviduct or culture medium and undergo oocyte aging, which impairs oocyte competence . In our facility, the percentage of blastocysts gradually worsened in a time‐dependent manner over a 5‐hour period before ICSI (data not shown).…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, optimization of oocyte aging should improve laboratory and clinical outcomes in assisted reproductive technology. However, in addition to factors that may adversely affect oocyte aging, extended in vitro culture may impair oocyte competence . For example, Wakayama et al reported negative effects of temperature change on mouse oocyte aging, while Goud et al indicated that the production of reactive oxygen species significantly enhanced oocyte aging.…”
Section: Introductionmentioning
confidence: 99%
“…As a woman gets older, an evident decrease in fecundity occurs in parallel, due to both a reduction of the ovarian follicle numbers and an impairment of oocyte quality as well. In particular, by age 35 a woman's chance of conceiving per month is decreased by half and, at the age of 45, the natural fertility rate per month drops to 1% [14]. Thus, postponing motherhood for social, educational or financial reasons may significantly decrease the chance for a woman to become pregnant and/or increase the risk of obstetric complications [15].…”
Section: Age-related Infertilitymentioning
confidence: 99%
“…In fact, up to one in six couples in Western countries is affected by infertility [7]. The most important risk factors in the development of female subfertility include: the age of the woman [6], ovulatory disorders, chromosomal abnormalities, and defective male fertility [8][9][10]. A widespread variety of environmental pollutants, such as several classes of pesticides, heavy metals, and air particulate matter plays a key role in the pathogenesis of female infertility [8,11,12].…”
Section: Introductionmentioning
confidence: 99%